Guided isolation of daphnane-type diterpenes from Daphne genkwa by molecular network strategies. (June 2022) - Mi, Si-Hui; Zhao, Peng; Li, Qian; Zhang, Hao; Guo, Rui; Liu, Yu-Yang; Lin, Bin; Yao, Guo-Dong; Song, Shao-Jiang; Huang, Xiao-Xiao
Abstract: A molecular networking-guided study on the Daphne genkwa Sieb. et Zucc led to the isolation of twelve daphnane-type diterpenoids including four undescribed compounds, yuanhuakines A–D. Their structures were elucidated by spectroscopic analyses, ECD calculations, and single-crystal X-ray diffraction analysis. All isolates were evaluated for their inhibitory activity against the A549, Hep3B, and MCF-7 cell lines. The majority of compounds inhibited A549 cells with IC50 values ranging from 7.77 to 20.56 μ M, and their structure-activity relationship is preliminarily discussed. Five of these compounds were selected for further experiments, and they appear to inhibit A549 cell lines by inducing apoptosis. Graphical abstract: Image 1 Highlights: Twelve daphne-type diterpenoids were isolated by molecular network strategies. One structure was elucidated by single-crystal X-ray diffraction analysis. The inhibitory activity of all isolates on A549, Hep3B, and MCF-7 was evaluated. The AV/PI double staining experiment revealed the mechanism of inducing apoptosis.